The mystery of the M74 syndrome solved: Plentiful fatty sprat as prey for salmon leads to reproduction disorder - Keinänen, Marja; Vuorinen, Pekka (Finnish Game and Fisheries Research Institute, 2012)
Thiamine (vitamin B1) deficiency results in mortalities of yolk-sac fry of salmon (M74). Deficiency of thiamine develops when the fat content of prey fish is high and the thiamine concentration too low in comparison to energy density and the content of unsaturated fatty acids. Abundance of young sprat as food for salmon increases the prevalence and severity of M74 and impairs the reproduction of Baltic salmon.
Press release 4.4.2012, Finnish Game and Fisheries Research Institute